1994
DOI: 10.1002/cne.903410202
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of primary afferent fibers projecting from hindlimb cutaneous nerves to the medulla oblongata in the cat and rat

Abstract: The dorsal column nuclear complex, one of the most important relays for tactile perception, has well been known to be somatotopically organized. Topographical arrangements of terminal sites of individual cutaneous nerves within the dorsal column nuclei, however, have not been examined systematically, although many studies have been done upon primary afferents to the medulla oblongata, including the dorsal column nuclear complex. Thus, in the present study, distribution of primary afferent fibers projecting fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 63 publications
(107 reference statements)
2
18
0
Order By: Relevance
“…Bilateral labeling was limited to the level of obex and just caudal to it. Results of the tracing study confirmed the bilaterality of these pathways suggested by the electrophysiological recordings, a finding consistent with two previous tracing studies (55,56), in which labeling also was seen to move bilaterally near the level of obex and no Gr labeling occurred by injecting just the motor branch of the perineal nerve (57).…”
Section: Penile Inputs To Nucleus Gracilissupporting
confidence: 90%
“…Bilateral labeling was limited to the level of obex and just caudal to it. Results of the tracing study confirmed the bilaterality of these pathways suggested by the electrophysiological recordings, a finding consistent with two previous tracing studies (55,56), in which labeling also was seen to move bilaterally near the level of obex and no Gr labeling occurred by injecting just the motor branch of the perineal nerve (57).…”
Section: Penile Inputs To Nucleus Gracilissupporting
confidence: 90%
“…Separate patches and clusters of neurons along the rostrocaudal axis of the nucleus receive inputs from the same skin regions. This is not only the case for the primates of the present study, but for other mammals as well (Maslany et al, 1991;Wessels et al, 1991;Ueyama et al, 1994). At a more detailed level of analysis, single afferents likely branch to innervate several cell clusters along the rostrocaudal axis of the gracile nucleus (for the cuneate nucleus, see Fyffe et al, 1986;Weinberg et al, 1990).…”
Section: Functional Implications Of the Anatomical Organization Of Thmentioning
confidence: 72%
“…Based on microelectrode recordings, Johnson et al (1968) described a mediolateral progression of representations in the gracile nucleus from tail to foot to leg, as in the present study. In the gracile nucleus of cats, Ueyama et al (1994) found that the dense foci of the terminal labeling from nerves innervating the distal parts of the hindlimb were located more dorsomedial than those of the nerves innervating the proximal parts, and label from the foot occupied a more extensive termination zone in the gracile nucleus than label from the proximal hindlimb. These results are in good agreement with our data from all four primate species studied.…”
Section: Gracile Nuclei Of Other Mammalsmentioning
confidence: 97%
See 1 more Smart Citation
“…Comparing with the neurons of the cell nest region, the receptive fields of the hair stimulation in the reticular region are larger, the dorsal column input to this region is lesser and not arranged somatotopically, the neurons of this region have large cortical input and a small proportion of its neurons contribute to the medial lemniscus fibers [30]. The physiological studies of the Gr in the cat showed also that the terminal ends of the nerve fibers which carry the sensation from the distal parts of the hindlimb ‖the foot‖ have more extensive representation at the Gr and are a located dorsomedial to those of the nerve fibers which carry the sensation from the proximal parts of the hinlimb [21,55]. …”
Section: Catsmentioning
confidence: 99%